(untitled) (Archive of Conferences, 2021)
The decisions that are being made today in the direction of education policy have a broad impact on the country’s scientific, economic, political and cultural needs,” said Darya columnist, expert of the Great Future Group, Busan, South Korea. Professor of the University of Languages Azamat Akbarov. The system of teaching foreign languages to children at an early age, which has been introduced in some countries of the world since the 1990s, is also in line with our country, and in 2017-2018 it was proposed to adopt some legislation in this area